The Burden of Gastrointestinal, Hepatobiliary and Pancreas Related Diseases and Their Causes at Tertiary Care Hospital in Karachi - Zakir, Muhammad Fahad; Karim, Shahid; Kalwar, Hamid Ali; Wadhwa, Rajesh kumar; Furqan, Muhammad; Baloch, Muhammad Hussain (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the burden of gastrointestinal, hepatobiliary and pancreas-related disease, frequencies and their presentations.Study Design: Cross-sectional study.Place and Duration of Study: Gastroenterology Department, Liaquat National Hospital, Karachi from Oct 2020 to Jul 2021Methodology: Patients aged ≥18 years, having diagnosis related to gastrointestinal, hepatobiliary and pancreas were included in the study. Demographic features, reasons for admission, and length of stay were recorded.Results: A total of 2183 patients were enrolled. Nearly half of the patients were ≥60 years. 43% of patients were presented with abdominal pain. The most frequent diagnosis includes decompensated chronic liver disease followed by upper gastrointestinal bleed. The proportion of female patients was significantly higher for gastritis (p=0.009) and acute cholecystitis (p=0.036), while males with Hepatitis-B (p=0.019) and liver abscesses (p=0.018) were significant. Admissions through emergency were higher for gastrointestinal bleeding and decompensated chronic liver disease (p